INNOVATIVE TRIAD: RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF LEVOSALBUTAMOL SULPHATE, AMBROXOL HYDROCHLORIDE AND GUAIPHENESIN IN ORAL LIQUID DOSAGE FORM - M., Selvakanimozhi; M., Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Levosalbutamol Sulphate, Ambroxol Hydrochloride, and Guaiphenesin together provide a comprehensive approach to the treatment of different respiratory disorders, symptom relief, and improved respiratory health. RP-HPLC has become a highly effective method with great resolution, sensitivity, and repeatability for analyzing complex mixtures. This paper describes the development and estimation of the RP-HPLC approach for the concurrent quantification of guaiphenesin, ambroxol hydrochloride, and levosalbutamol sulphate in bulk and medicinal dose form. The chromatographic separation was performed with HPLC agilent 1100 series with DAD detector, EZ Chromelite software was used for the chromatogram identification. The stationary phase used was C-18 inertsil column of dimension 250 × 4.6 mm with particle sizes of 5µ. The mobile phase used was buffer, acetonitrile and methanol in the ratio of (65:10:25). The developed method produced chromatogram with perfect sharp peaks, and with good resolution and minimal tailing. The retention time of Levosalbutamol sulphate, guaiphenesin and ambroxol hydrochloride was found to be 2.853, 8.273 and 12.273 respectively. The method was linear with the correlation coefficient value of 0.9999. The system suitability parameters were found to be within the acceptable criteria. In summary, we have developed a robust analytical approach that can reliably and accurately quantify these active components through rigorous method development and validation procedures. The findings of the technique validation, carried out in compliance with ICH principles, have shown that the approach is suitable for routine quality control analysis and that the results fall within acceptable bounds.